CORRECTION OF FUNCTIONAL SYMPTOMS OF CHANGES IN THE MOVEMENT PATTERN OF THE LOWER EXTREMITY IN ELDERLY PATIENTS WITH KNEE JOINT ENDOPROSTHESIS IN THE REMOTE POSTOPERATIVE PERIOD BY PHYSICAL THERAPY - Petruniv, Kh. V. (Rehabilitation and Recreation, 2023)
Purpose: to assess the effectiveness of the developed physical therapy program on the parameters of functional symptoms and changes in the movement pattern of the lower limb in elderly patients with knee arthroplasty in the remote period after surgical intervention. Methods. 80 elderly people were examined. The control group consisted of 24 people without joint endoprostheses, with no signs of sarcopenia. The comparison group consisted of individuals with knee arthroplasty and sarcopenia with low rehabilitation compliance with regard to active rehabilitation intervention. Representatives of the main group with knee endoprosthesis and sarcopenia practiced according to a developed program of physical therapy, created taking into account the specifics of each comorbid condition. The program lasted 6 months; contained the following elements: therapeutic exercises, functional training, massage, kinesiotaping; dietary recommendations; patient education. The effectiveness of the program was evaluated according to the dynamics of Forgotten Joint Score-12, Knee Society Score, goniometry of the knee joint, manual muscle testing of the thigh muscles. Results. In elderly patients with knee endoprosthesis and sarcopenia, functional symptoms of changes in the movement pattern of the lower limb in the form of a violation of the structural and functional state of the knee joint, joint contracture, and a decrease in the strength of the hip muscle groups were revealed. The developed physical therapy program revealed a statistical improvement in the condition of patients due to the influence on the components of the movement pattern of the knee joint due to the improvement of the functional state of the knee joint, improvement of its flexibility, strength of the thigh muscles, reduction of pain in comparison with the initial indicators for all the studied parameters (р<0 .05); however, the indicators of the control group were not reached (p>0.05). Low rehabilitation compliance of patients in the comparison group, despite being aware of the risks of polymorbidity, was associated with a lack of improvement over a similar follow-up period. Conclusions. Elderly patients with the consequences of total knee arthroplasty and sarcopenia require the development of physical therapy programs taking into account and correcting the specifics of each condition, the presence of physical status disorders and the risk of falling, which will increase the overall effectiveness of rehabilitation measures.